Recent advances on 3D printing of patient-specific implants for fibrocartilage tissue regeneration. Issue 3 (14th August 2018) - Costa, João B; Silva-Correia, Joana; Reis, Rui L; Oliveira, Joaquim M
Fibrocartilage is a very peculiar type of tissue found in intervertebral disc and meniscus. It is characterized by its avascular nature and for the shear and compressive forces that it can be subjected to. The number of individuals affected by the degeneration of fibrocartilaginous tissues has been growing and the poor outcomes of current treatments have led to an increased interest in new alternative approaches. Therefore, the combination of reverse engineering with 3D printing has been extensively explored in order to produce patient-specific implants capable of improving the current clinical outcomes. This review outlines the recent advances achieved in the tissue engineering field, especially focusing on fibrocartilaginous tissue.